Setting and timing of gold mineralization in the Jiadong and Liaodong Peninsulas, North China Craton. - Zhang, Xiao'ou (Curtin University, 2002)
The primary objective of this thesis was to date the age of gold mineralization in the Jiaodong and Liaodong Peninsulas, China. Based on SHRIMP U-Pb zircon ages of dykes and host rocks at 13 gold deposits in the two peninsulas and the 40(subscript)Ar-39(subscript)Ar dating of sericite at the Cangshang deposit in the Jiaodong Peninsula, a single gold mineralization event at ca. 122 - 119 Ma has been identified.Ten gold deposits in the Jiaodong Peninsula and three gold deposits in the Liaodong Peninsula were examined. Gold mineralization can be divided into the disseminated-and-veinlet type (Jiaojla-style) and vein type (Linglong-style) and all these deposits are strongly controlled by faults. The most common host rocks are granitoids, with a SHRIMP 206(subscript)Pb/238(subscript)U age of 150 - 165 Ma. The youngest host rocks in the Jiaodong Peninsula are granodiorite, with an age of ca. 128 Ma. The oldest dated host rock in the Jiaodong Peninsula is amphibolite with a metamorphic zircon age of 1852 plus or minus 37 Ma; in the Liaodong Peninsula, the oldest host rock is metasandstone with the youngest detrital zircon giving an age of 1886 plus or minus16 Ma. The Jiaodong and Liaodong Peninsulas are underlain by Precambrian basement with components up to ca. 3.7 Ga old and these are reflected in the zircon population. There are three main peaks of inherited zircons, which yield Late Archaean (ca. 2500 Ma), Palaeoproterozoic (1800-2200 Ma) and Early Mesozoic (ca. 200-250 Ma) ages.The close spatial and temporal relationships between dykes and gold mineralization has only recently been recognized in China. Based on the cross-cutting relationship between dykes and gold lodes (and the alteration style of dykes), three types of dykes are recognized: pre-, syn- and post-mineralization dykes. Premineralization dykes yield an age of ca. 124 Ma; syn-mineralization dykes give an age of ca. 122-119 Ma, which can also be interpreted as the time of gold mineralization; further work is needed to date post-mineralization dykes, since no suitable samples were identified during this study.40(subscript)Ar-39(subscript)Ar dating of sericite has been used to determine the timing of gold mineralization at the Cangshang Gold Deposit. It gives a well-defined 40(subscript)Ar-39(subscript)Ar age of 121.3 plus or minus 0.2 Ma.The second objective of this thesis was to understand why the tectonic setting of the Jiaodong and Liaodong Peninsulas is favourable for gold formation and what is a sound genetic model for these gold deposits. Based on this study, it is interpreted that multiple orogenic events created a favourable tectonic environment for the Jiaodong and Liaodong gold deposits. It is suggested that delamination related to orogenic events occurred beneath the Jiaodong and Liaodong Peninsulas. The substantial heat and fluid transfer caused by delamination allowed mantle-derived magma and auriferous fluids to be channelled along deep faults to favourable structures within the crust. This probably explains why the dykes and gold lodes are closely associated in both time and space.